2020
DOI: 10.1108/ijlm-01-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain resilience: an adaptive cycle approach

Abstract: PurposeThe purpose of this paper is to develop a conceptual framework for extending an understanding of resilience in complex adaptive system (CAS) such as supply chains using the adaptive cycle framework. The adaptive cycle framework may help explain change and the long term dynamics and resilience in supply chain networks. Adaptive cycles assume that dynamic systems such as supply chain networks go through stages of growth, development, collapse and reorientation. Adaptive cycles suggest that the resilience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 81 publications
0
65
0
1
Order By: Relevance
“…Therefore, focusing on a scale of analysis consistent with the objectives of a focal firm is not sufficient to understand or describe the outcomes associated with these interactions at the scale of the supply chain. A deeper understanding of supply chain resilience and sustainability should recognize interactions that involve multiple nested scales and levels (Carter et al, 2015; Adobor and McMullen, 2018; Meschnig et al, 2018; Adobor, 2020; Wieland, 2021). Likewise, research focused on building upon the boundary conditions of a supply chain per Carter et al (2015) is also needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, focusing on a scale of analysis consistent with the objectives of a focal firm is not sufficient to understand or describe the outcomes associated with these interactions at the scale of the supply chain. A deeper understanding of supply chain resilience and sustainability should recognize interactions that involve multiple nested scales and levels (Carter et al, 2015; Adobor and McMullen, 2018; Meschnig et al, 2018; Adobor, 2020; Wieland, 2021). Likewise, research focused on building upon the boundary conditions of a supply chain per Carter et al (2015) is also needed.…”
Section: Discussionmentioning
confidence: 99%
“…Christopher and Peck, 2004; Williams et al, 2009; Voss and Williams, 2013; Wieland, 2013; Heckman et al, 2015; Hohenstein et al, 2015; Ivanov et al, 2017; Linnenluecke, 2017; Kochan and Nowicki, 2018). Nonetheless, there is a need to improve our understanding of the linkages between resilience and the multiscale dynamics that explain how supply chains evolve over time and space, as recognition of the multiscale dynamic interactions that characterize supply chains as CASs is still missing (Carter et al, 2015; Adobar and McMullen, 2018; Meschnig et al, 2018; Adobar, 2020). We believe that incorporating the concepts of scale and mismatched scales into discussions of supply chain resilience is an essential part of broadening our understanding of these linkages.…”
Section: Contemporary Conceptualizations Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Supply chain resilience is the capability of a supply chain to cope with unforeseen, disrupting events and to recover quickly to its original level of performance, or to a new level required to maintain the expected operating, financial, and market performance (Adobor, 2020;Ponomarov & Holcomb, 2009). To build a resilient supply chain, firms need to identify and assess the nodes for risks, their severity, and the likelihood of occurrence, and how these risks can be detected (Dubey et al, 2017;Chang et al, 2015).…”
Section: Supply Chain Resiliencementioning
confidence: 99%
“…Blecker (2007) and Adobor (2020) found that logistical work is a type of service. The service sector is recognized as very important to be part of today's industrialized economy.…”
Section: Literature Reviewmentioning
confidence: 99%